A Latin American, Portuguese and Spanish consensus on a core communication curriculum for undergraduate medical education - Garcia de Leonardo, Cristina; Ruiz-Moral, Roger; Caballero, Fernando; Cavaco, Afonso; Moore, Philippa; Paula Dupuy, Lila; Pithon-Cyrino, Antonio [UNESP]; Teresa Cortes, Ma; Gorostegui, Marilen; Loureiro, Elizabete; Bosch Fontcuberta, Josep Ma; Casasbuenas Duarte, Luis; et al. (Biomed Central Ltd, 2016)
Background: To present learning outcomes in clinical communication for a Core Curriculum for medical undergraduate students in Latin America, Portugal and Spain (LAPS-CCC) and to establish an expert network to support a transnational implementation. Methods: Through an iterative process, an international group of 15 experts developed an initial set of learning outcomes following a review and discussion of relevant international and local literature. A two-round Delphi survey involving 46 experts from 8 countries was performed. Quantative and qualitative analisis permited the definition of the final consensus. Results: The initial proposal included 157 learning outcomes. The Delphi process generated 734 comments and involved the modification, deletion and addition of some outcomes. At the end of the process, a consensus was reached on 136 learning outcomes grouped under 6 competency domains with a high overall acceptance (95.1 %). Conclusions: The learning outcomes of this proposal provide a guide to introduce, support and develop communication curriculae for undergraduate medical studies in the countries involved or in other Spanish-or Portuguese-speaking countries.
Keywords: Physician patient communication; Interpersonal skills; Health communication; Delphi technique; Consensus method; Medical education; Medical curriculum; Learning outcomes